Effects of oligo sequence and chemistry on the efficiency of oligodeoxyribonucleotide-mediated mRNA cleavage. - Baker, C (1990)
Using the endogenous histone H4 mRNA of Xenopus oocytes as a target, we have previously shown that 20mer oligos complementary to different parts of this sequence vary in their effectiveness at causing mRNA cleavage in vivo, and that some of the RNA can never be cleaved. In this paper we show that the resistant RNA is not localised within one part of the oocyte, and that the relative resistance in vivo of endogenous or synthetic H4 mRNA to the different oligos is preserved in an in vitro assay system using deproteinised RNA. If an prior annealing step is included in vitro, all resistance is abolished. Chemical modification of one oligo by end substitution with methylphosphonate or phosphorothioate residues did not improve cleavage efficiency. Oligos with complete phosphorothioate substitution cause slower cleavage in vivo but persist for longer. Consequently phosphorothioate oligos are effective at lower doses than phosphodiester ones, provided that the incubation time is long enough (24 hours). Increasing oligo length from 20nt to 30nt increases phosphorothioate oligo efficiency over long reaction times in vivo, but decreases efficiency during short in vitro assays. Similar increases in length did not affect phosphodiester oligo performance in vivo, but caused a decrease in efficiency in vitro which was overcome by an annealing step.